PENGARUH PENERAPAN PENGENDALIAN INTERNAL DAN PERSONAL CULTURE TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (Studi Kasus Pada Usaha Furniture Siro Pagar Abadi Malang) - Anissa Trias Febrianti; Noor Shodiq Askandar; Abdul Wahid Mahsuni (Universitas Islam Malang, 2021)
The tendency to cheat accounting is common in new companies or businesses that even go public. There are many things that could affect the lack of optimal internal control of a company and the lack of level of personal honesty in an employee's terms. The research was intended to see and analyze the effects of applying internal and personal culture control to the tendency to cheat accounting. Based on the results of test t studies, there have been significant effects between the variables of the application of internal and personal control. And test f shows a common influence on the tendency to cheat accounting. Meaning that the higher the level of internal control of the company or the effort and effort to create a positive personal culture environment is expected to make it a corporate strategy in the minimize of the disproportionate tendency to accounting to a company.Keywords: Tendency to Cheat Accounting, To Apply Internal Control, Personal Culture.